Effects of streamlining a bluff body in the laminar vortex shedding regime - Dobriyal, Ritvik; Mishra, Maneesh; Bölander, Markus; Skote, Martin (American Society of Mechanical Engineers (ASME), 2019)
Two-dimensional flow over bluff bodies is studied in the unsteady laminar flow regime using numerical simulations. In previous investigations, lift and drag forces have been studied over different cross section shapes like circles, squares and ellipses. We aim to extend the previous research by studying the variation of hydrodynamic forces as the shape of the body changes from a circular cylinder to a more streamlined or a bluffer body. The different body shapes are created by modifying the downstream circular arc of a circular cylinder into an ellipse, hence elongating or compressing the rear part of the body. The precise geometry of the body is quantified by defining a shape factor. Two distinct ranges of shape factors with fundamentally different behavior of lift and drag are identified. The geometry constituting the limit is where the rear part ellipse has a semi minor axis of half the radius of the original circle, independent of the Reynolds number. On the other hand, the vortex shedding frequency decreases linearly over the whole range of shape factors. Furthermore, the variation of the forces and frequency with Reynolds number, and how the relations vary with shape factor are reported.
Keywords: Vortex shedding; Shapes; Circular cylinders; Drag (Fluid dynamics); Geometry; Reynolds number; Computer simulation; Flow (Dynamics); Fluid-dynamic forces; Laminar flow